The Recent Location of Foreign R&D Activities by Large MNCs in the European Regions. The Role of Different Sources of Spillovers - John A. Cantwell; Lucia Piscitello (European Regional Science Association (ERSA), 2003)
This paper examines the recent siting of foreign-owned corporate technological development in European regions. The data used are patents granted in the US to the world's largest firms in the period 1987-'95. According with the literature on knowledge creation in MNCs, we find that location of foreign-owned research tends to agglomerate, depending upon the potential for different sources of spillovers. Specifically, we find that location decisions are positively influenced by intra- and inter-industry spillovers, and the local scientific and educational infrastructure.
Keywords: 330